2014
DOI: 10.1371/journal.pone.0104524
|View full text |Cite
|
Sign up to set email alerts
|

A Yersinia pestis tat Mutant Is Attenuated in Bubonic and Small-Aerosol Pneumonic Challenge Models of Infection but Not As Attenuated by Intranasal Challenge

Abstract: Bacterial proteins destined for the Tat pathway are folded before crossing the inner membrane and are typically identified by an N-terminal signal peptide containing a twin arginine motif. Translocation by the Tat pathway is dependent on the products of genes which encode proteins possessing the binding site of the signal peptide and mediating the actual translocation event. In the fully virulent CO92 strain of Yersinia pestis, the tatA gene was deleted. The mutant was assayed for loss of virulence through var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 90 publications
1
20
0
Order By: Relevance
“…Furthermore, the tatA mutated bacteria could not be detected in the draining lymph node or the spleen of mice 48 hours after s.c. inoculation with high doses (10 7 cfu/mouse), similar to the observations reported with respect to the nlpD mutated bacteria [20]. The results obtained with the s.c. administration of the TatA mutant are consistent with those of Bozue and colleagues [61], who showed that a Y . pestis CO92 tatA mutant was severely attenuated upon subcutaneous infection of Swiss Webster mice.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Furthermore, the tatA mutated bacteria could not be detected in the draining lymph node or the spleen of mice 48 hours after s.c. inoculation with high doses (10 7 cfu/mouse), similar to the observations reported with respect to the nlpD mutated bacteria [20]. The results obtained with the s.c. administration of the TatA mutant are consistent with those of Bozue and colleagues [61], who showed that a Y . pestis CO92 tatA mutant was severely attenuated upon subcutaneous infection of Swiss Webster mice.…”
Section: Resultssupporting
confidence: 90%
“…Tat substrates function in energy metabolism, cellular division, motility and adaptation to environmental stress [52,58]. The system has been shown to be important for virulence in many bacterial pathogens including Yersinia species [25,52,59,60,61].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…B. pseudomallei 1026b ( 26 ), F. tularensis Schu S4 ( 27 ), and Y. pestis CO92 ( 28 ) were grown until mid-log phase. Bacterial doses and the infection routes used were based on previous studies (Table 4) ( 26 , 29 31 ).…”
Section: Methodsmentioning
confidence: 99%